Association of mean arterial pressure with 5-year risk of incident diabetes in Chinese adults：a secondary population-based cohort study. Issue 9 (19th September 2022) - Wu, Yang; Hu, Haofei; Cai, Jinlin; Chen, Runtian; Zuo, Xin; Cheng, Heng; Yan, Dewen
Abstract : Objective: Hypertension predicts the development of diabetes. However, there are still lacking high-quality studies on the correlation between mean arterial pressure (MAP) and incident diabetes. We aimed to explore the relationship between MAP and diabetes in Chinese adults. Design: This is a secondary retrospective cohort study and the data were downloaded from the 'DATADRYAD' database (www.Datadryad.org ). Participants: The study included 210 418 adults without diabetes at baseline between 2010 and 2016 across 32 sites and 11 cities in China. Setting: The target-independent and dependent variables were MAP measured at baseline and diabetes occurred during follow-up. Cox proportional hazards regression was used to explore the relationship between MAP and diabetes. Primary outcome measures: The outcome was incident diabetes, which was defined as fasting blood glucose ≥7.00 mmol/L and/or self-reported diabetes during follow-up. Patients were censored either at the time of the diagnosis or at the last visit, whichever comes first. Results: 3927 participants developed diabetes during a 5-year follow-up. After adjusting covariates, MAP positively correlated with diabetes (HR=1.008, 95% CI 1.005 to 1.011, p<0.001), and the absolute risk difference was 0.02%. E-value analysis and multiple imputations were used to explore the robustness of the results. The relationship between MAP and diabetes was also non-linear, and the inflection point of MAP was 100.333 mm Hg. Subgroup analysis revealed a stronger association between MAP and diabetes in people with age (≥30, <50 years old), fasting plasma glucose <6.1 mmol/L and drinking. Additionally, receiver operating characteristic (ROC) curves showed the predictive performance of MAP for diabetes was similar to systolic blood pressure (SBP) (area under the curve (AUC)=0.694 with MAP vs AUC=0.698 with SBP). Conclusions: MAP is an independent predictor for a 5-year risk of incident diabetes among Chinese adults. The relationship between MAP and diabetes is also non-linear. When MAP is below 100.333 mm Hg, MAP is closely positively related to diabetes.